The Musical Treasure-Trove of Uzbekistan: The Phenomenon of Uzbek Classical Music. Issue 1 (2nd January 2016) - Matyakubov, Otanazar
Abstract : This article, derived from a chapter in the book Musical Treasure-Trove of Uzbekistan, addresses the history, sources, theory, and practice of the Uzbek classical music called makom [ maqâm ]. The author argues that Uzbek classical music has an unbroken, complex, and philosophical legacy that has come down to us as a living tradition from numerous sources in the wider region of Central Asia. He illustrates his innovative interpretation with diverse music samples and elaborate analysis of makom terminology.